2020
DOI: 10.1021/acs.est.0c02651
|View full text |Cite
|
Sign up to set email alerts
|

Superselective Removal of Lead from Water by Two-Dimensional MoS2 Nanosheets and Layer-Stacked Membranes

Abstract: Point-of-use (POU) devices with satisfactory lead (Pb 2+ ) removal performance are urgently needed in response to recent outbreaks of lead contamination in drinking water. This study experimentally demonstrated the excellent lead removal capability of two-dimensional (2D) MoS 2 nanosheets in aqueous form and as part of a layer-stacked membrane. Among all materials ever reported in the literature, MoS 2 nanosheets exhibit the highest adsorption capacity (740 mg/g), and the strongest selectivity/affinity towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 61 publications
3
57
0
Order By: Relevance
“…Actually, a downward shift of binding energy has been observed in the case of Pb( ii ) removal by MoS 2 , in which Pb( ii ) binds to two neighboring S atoms with an equal bond length. 40 Hg( ii ) as a larger and softer Lewis acid is more likely to form a multi-bonding structure with S, in a similar manner to S–Hg–S arranged in a square planar configuration on the galena surface. 60 The TEM elemental mapping (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Actually, a downward shift of binding energy has been observed in the case of Pb( ii ) removal by MoS 2 , in which Pb( ii ) binds to two neighboring S atoms with an equal bond length. 40 Hg( ii ) as a larger and softer Lewis acid is more likely to form a multi-bonding structure with S, in a similar manner to S–Hg–S arranged in a square planar configuration on the galena surface. 60 The TEM elemental mapping (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MoS 2 nanosheets were prepared by an established chemical exfoliation method following the approach reported previously, and the schematic illustration of the exfoliation process is shown in Fig. S1 † 40 . Briefly, 5 mL of 1.6 M n -butyllithium in hexane solution was added to ∼300 mg of bulk MoS 2 powder (∼2 µm, Sigma-Aldrich) and the suspension was stirred gently in a nitrogen-filled glovebox for 2 d. Then 40 mL hexane was added to the resulting solution mixture, and the excess organic reactants and byproducts were removed by centrifugation at 4000 rpm for 15 min to obtain the Li-intercalated MoS 2 sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of such a negative charge was established as a result of several examples of cationic species being encapsulated in MoS 2 structure [58,62–64] . Studies related to the surface charge of MoS 2 nanosheets have also shown that their dispersion maintains a negative zeta potential [65–68] . In addition, exfoliation of MoS 2 results in numerous defects such as sulphur vacancies in its surface [69,70] .…”
Section: Resultsmentioning
confidence: 99%